The Temple Veil as a Spatial Icon. Revealing an Image-Paradigm of Medieval Iconography and Hierotopy - Lidov, Alexei (IKON, 2014)
Abstract The author argues that the imagery of the Sacred Veil separating the Holy from the Holy of Holies at the Jewish Temple in Jerusalem was a very powerful spatial icon which considerably influenced art and culture of the Byzantine world and the Latin West. The paper deals with new approaches to the history of art, and the crisis in traditional methodology which does not work in some cases. First of all, it concerns the concept of hierotopy (the creation of sacred spaces), recently proposed by the author of this paper and elaborated in several publications by the international group of scholars (www.hierotopy.ru). These studies have revealed an important theoretical issue. In many cases the discussion of visual culture can not be reduced to a positivist description of artifacts, or to the analysis of theological notions. Some phenomena can be properly interpreted only on the level of “image-paradigms”, which do not coincide with the illustrative pictures or ideological conceptions. This special notion seems a useful instrumentum studiorum, which helps to explain a layer of phenomena. That image-paradigm was not connected with the illustration of any specific text, though it was a part of a continuum of literary and symbolic meanings and associations. This type of imagery is quite distinct from what one could call an iconographic device. At the same time the image-paradigm belonged to visual culture, it was visible and recognizable, but it was not formalized in any fixed state, either in a form of the pictorial scheme or in a mental construction. In this respect the image-paradigm looks similar to the metaphor that loses its sense in re-telling, or in its de-construction into parts. It does not concern any mystic but a special type of consciousness, which determined several symbolic structures as well as numerous concrete pictorial motives; it challenges our fundamental methodological approach to the image as illustration and flat picture. Abstract U ovome se radu raspravlja o tome kako je prikaz Presvetog Zastora koji razdvaja Svetište od Svetišta nad svetištima u židovskome Hramu u Jeruzalemu bio najmoćnija prostorna ikona, koja je znatno utjecala na umjetnost i kulturu bizantskoga prostora, ali i latinskoga Zapada. U članku se preispituju novi pristupi povijesti umjetnosti i kriza tradicionalne metodologije, koja u pojedinim slučajevima ne daje željene rezultate. To se ponajprije odnosi na koncept hijerotopije (stvaranje svetog prostora), pojma koji je recentno uveo u raspravu autor ovoga članka i koji je međunarodna skupina znanstvenika elaborirala u nekoliko publikacija (www.hierotopy.ru). Te su studije ukazale na postojanje značajnog teorijskog problema. U mnogim se slučajevima rasprave o vizualnoj kulturi ne mogu svesti na pozitivističke opise djela ili na analizu teoloških pojmova. Neki se fenomeni mogu pravilno tumačiti samo na razini “slikovnih paradigmi”, što se ne podudara s ilustrativnim slikama ili ideološkim koncepcijama. Ova se posebna ideja čini korisnim instrumentum studiorum, koji pomaže objasniti slojeve fenomena. Iako “slikovna paradigma” nije povezana s ilustracijom određenoga teksta, dio je kontinuiteta literarnih i simboličkih značenja i asocijacija. Ova je vrsta prikaza različita od onoga što se može nazvati ikonografskim modelom. “Slikovna paradigma” pripada vizualnoj kulturi, ona je vidljiva i prepoznatljiva, ali nije formalizirana u nekom fiksnom obliku, niti kao slikovna shema niti kao misaona konstrukcija. U tom smislu nalikuje metafori koja gubi svoj smisao u prepričavanju ili u dekonstrukciji.